Neutrophil‐to‐lymphocyte ratio for predicting palliative chemotherapy outcomes in advanced pancreatic cancer patients. (12th February 2014) - Xue, Peng; Kanai, Masashi; Mori, Yukiko; Nishimura, Takafumi; Uza, Norimitsu; Kodama, Yuzo; Kawaguchi, Yoshiya; Takaori, Kyoichi; Matsumoto, Shigemi; Uemoto, Shinji; Chiba, Tsutomu
Abstract Several previous studies reported that the neutrophil‐to‐lymphocyte ratio (NLR) could be a promising prognostic factor for patients with cancer. We aimed to determine the prognostic value of NLR in patients with advanced pancreatic cancer (APC) following palliative chemotherapy. We retrospectively reviewed 252 consecutive APC patients receiving palliative chemotherapy between January 2006 and December 2012. We classified the patients according to the pretreatment NLR values (≤5 or >5) into two groups and investigated the difference in treatment outcomes, including time to treatment failure (TTF) and overall survival (OS). A total of 212 patients had pretreatment NLR values of ≤5 (group A), while 40 patients had an NLR of >5 (group B). TTF and OS were significantly shorter in group B than in group A (3.1 vs. 8.7 months and 6.0 vs. 12.8 months, respectively; both P < 0.01). After adjustment for putative prognostic factors, including distant metastasis, status of recurrent/unresectable disease, pretreatment carbohydrate antigen 19‐9 levels, and carcinoembryonic antigen levels using the Cox regression model, elevated pretreatment NLR remained an independent poor prognostic factor for OS (hazard ratio, 1.92; 95% confidence interval, 1.27–2.90; P < 0.01). In addition, patients in group B whose NLR dropped to ≤5 before the second cycle of chemotherapy showed longer TTF and OS compared with those whose NLR remained at >5. Our results support the idea that NLR can be a promising prognostic and predictive marker for APC patients receiving palliative chemotherapy.